Рапунцель: [для чтения взрослыми детям : перевод с немецкого] / Братья Гримм - Гримм Вильгельм Карл (Читаем сами, 2016)
Экземпляры: (20171109) / Инвентарный номер: 4864 / Цена: / Сис.шифр: 84.(4) / Авт.знак: Г84 / ГРНТИ: 17.82 / ББК: 84 (4)